INDEPENDENTLY FEED LIVESTOCK GROUP DUCK’S STARTER IN BOROGRAGAL VILLAGE - khusnul khotimah; Ahmad Amilin; Fitriana Apebruarin; Bintan Prayunantyo; Muhammad Reshtu Alam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Duck role as a producer of meat in Indonesia, according to statistics in 2010 remained low at only can meet the needs of 6.4 thousand tons from 14.3 thousand tons duck, so the lack of meat reached 7.9 thousand tons. Prospects duck broiler farming is very promising, especially in the area of Malang city and surrounding areas including travel Batu city, which has a lot of demand for broiler ducks in line with the increasing number of food stalls vegetables there. The location is at the community service Borogragal village, Donowarih Village, District Karangploso, Malang city. The main goal of this program is a community service Borogragal village particularly broiler breeding ducks. This community service is a core problem faced with the high cost of raising broiler ducks and waste for animal feed which has not been managed well. Of the existing problems, we provide alternative solutions to the problem of the program activities of community service by using probiotics as a mixture of waste used as animal feed ducks broiler by the way to ferment the waste, with the hope that the public can examine the use of waste as animal feed, knowing excellence probiotics as a mixture of animal feed, as well as capable of producing probiotic independently. The results of this public service activities in the form of probiotics used in mixed feed using household waste from villagers borogragal itself and agricultural waste in the village. On the other hand, the feed waste is fermented using probiotics able to be digested well by the ducks and can reduce feed costs incurred for breeding ducks. It tersebt evidenced by FCR obtained value is 2.85 with a value of SR 91.6%, it can reduce the cost of production and improve incomes. Besides his herd hamlet formed Borogragal able to enhance the spirit of the community to produce cattle back.